Subsurface methane sources and migration pathways within a gas hydrate mound system, Gulf of Mexico. (23rd January 2014) - Wilson, Rachel M.; Macelloni, Leonardo; Simonetti, Antonello; Lapham, Laura; Lutken, Carol; Sleeper, Ken; D'Emidio, Marco; Pizzi, Marco; Knapp, James; Chanton, Jeff
<x xml:space="preserve">Abstract</x> [1] Geochemical profiles were coupled with seismic information to examine subsurface hydrocarbon source, migration, and fate at a Gulf of Mexico carbonate‐gas hydrate mound (Woolsey Mound). Three seafloor features were investigated in detail: (1) major faults resulting from a rising salt body, (2) an acoustic backscatter anomaly, and (3) a pockmark associated with a major fault. We analyzed sulfate, chloride, dissolved inorganic carbon, and hydrocarbon concentrations, and carbon isotopes in pore water extracted from 20 m piston cores to characterize gas source and calculate methane flux. Dissolved biogenic methane dominated the off‐fault sites, while the contribution of thermogenic methane increased near a major fault where thermogenic gas hydrates were recovered. Within the pockmark, methane concentrations were low and isotopes indicated a biogenic source. Since pockmarks are typically formed from expulsive fluid flow, this suggests that either the pockmark is the legacy of a conduit that has become plugged or that the expulsed fluid is confined within the fault walls. At the acoustic anomaly, nonsteady state sulfate profiles suggested temporal variability in methane flux. Estimates from >75 gravity cores collected across Woolsey Mound since 2002 were mapped to display the spatial variability in methane flux relative to the faults. Methane flux to the seafloor was generally low, but increased several fold near the faults suggesting that the faults may provide conduits for hydrocarbons to bypass the "microbial biofilter" and cross the sediment water interface.